El rito del «palo volador»: encuentro de significados - Nájera Coronado, Martha Ilia (Revista Española de Antropología Americana, 2008)
The rite of the «Palo Volador», which has a prehispanic origin, was broadly diffused in Mesoamerica; given its spectacular character, it was mentioned in several historical sources since the beginnings of the Colonial period by friars, travelers and, of course, by diverse scholars until our days. In this article I intend to approach its meaning, based in comparative, synchronic and diachronic analyses, to propose that they do not only replay creation myths, but rather they represent two opposed symbolic models and bring an agreement with the participants assumed identity. One of these models is related with the celestial and masculine forces, and the other one with the underground world, the femininity and the anomalous things. In this context, I will try to search the symbolic place of the men that acquire the identity of simians during their flight inside one of the mentioned models.